"Someone Just Like Me": Narrative, Figured World, and Uptake in Therapeutic Books for Youths With Mental Health Disorders. (January 2017) - Smart, Graham; Thompson, Richard
This study extends a line of inquiry established by researchers using narrative theory to investigate the discourses of psychiatry. Drawing primarily on theories of narrative and genre, the study analyzes a series of autobiographical books intended for an audience of youth suffering from mental illness. Our research investigates how the rhetorical design of the books harnesses the discursive affordances of autobiographical narrative to encourage a particular uptake on the part of a reader suffering from mental illness. Performing an analysis of four of the books in the series, we found them to exhibit a design in which autobiographical narrative is used to prompt an anticipated uptake by the reader: motivation to commit to therapy and engage in lifelong self-care. The study offers insights to authors producing texts intended to support psychiatric practitioners in guiding youth toward recovery from mental illness.